DINASTI POLITIK PADA KEPEMIMPINAN PRESIDEN JOKOWI AKIBAT KONTESTASI POLITIK LOKAL GIBRAN-BOBBY - Aan Suryatwan (Journal Publicuho, 2020)
After the new order, general elections (Pemilu) were directly elected by the people in the reform era. Nevertheless, the phenomenon of political dynasties did not just disappear. A ruler with the hand of his power can still do much. Although he is not the one who directly elects public positions, maintaining his power can influence the political process, including local political contestation. In this study using descriptive qualitative through the study of literature with the aim that researchers can explore the potential of President Jokowi's political dynasty. The nomination of Gibran and Bobby presented criticisms of President Jokowi's image, political ethics, and leadership. Political officials born from political dynasties usually do not perform well. That can happen to Gibran and Bobby if elected to political contestation.